Role of genetic testing in the management of indeterminate thyroid nodules in the Indian setting - Jeyashanth Riju; Nihal Thomas; Thomas V Paul; Deepak Thomas Abraham; Rekha Pai; Anne J Prabhu; Paul Mazhuvanchary Jacob; Remya Rajan; Rajiv C Michael; Amit Jiwan Tirkey; Natarajan Ramalingam; Hesarghatta S Asha; et al. (Indian Journal of Endocrinology and Metabolism, 2024)
The increased detection of thyroid nodules in the human population has led to an increase in the number of thyroid surgeries without an improvement in survival outcomes. Though the choice for surgery is straightforward in malignant thyroid nodules, the decision is far more complex in those nodules that get categorized into indeterminate thyroid nodules (ITN) by fine needle aspiration. Therefore, there is a pressing need to develop a tool that will aid in decision-making among the ITN. In this context, the development of various molecular testing (MT) panels has helped to confirm or rule out malignancy, reducing unnecessary surgeries and potentially guiding the extent of surgery as well. Currently, such tests are widely used among the Western population but these MT panels are not used by the South Asian population because of non-availability of validated panels and the high cost involved. There is a need to develop a suitable panel which is population-specific and validate the same. In this review, we would focus on current trends in the management of ITN among the South Asian population and how to develop a novel MT panel which is cost-effective, with high diagnostic accuracy obviating the need for expensive panels that already exist.